2009
DOI: 10.1017/s175173110900473x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of methane emission from beef cattle using data measured in indirect open-circuit respiration calorimeters

Abstract: The objectives of the present study were to examine relationships between methane (CH 4 ) output and animal and dietary factors, and to use these relationships to develop prediction equations for CH 4 emission from beef cattle. The dataset was obtained from 108 growing-to-finishing beef steers in five studies and CH 4 production and energy metabolism data were measured in indirect respiration calorimeter chambers. Dietary forage proportion ranged from 29.5% to 100% (dry matter (DM) basis) and forages included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
74
4
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 14 publications
15
74
4
2
Order By: Relevance
“…A higher R 2 might be expected as measured data for in vivo rumen digested OM converted to VFA, as well as measured molar proportions of VFA were used as an input for the calculations. However, it was well within R 2 obtained with other models predicting CH 4 production from intake parameters (Yan et al, 2009;Nielsen et al, 2013) and most likely caused by variation in the measurement of rumen VFA and OM digestion as demonstrated before in a theoretical simulation study by Bannink et al (2006). Using l CH 4 /kg DMI as the unit strongly decreased variation compared with l CH 4 /day because DMI is the major determinant for variation in CH 4 production.…”
Section: Discussionsupporting
confidence: 84%
“…A higher R 2 might be expected as measured data for in vivo rumen digested OM converted to VFA, as well as measured molar proportions of VFA were used as an input for the calculations. However, it was well within R 2 obtained with other models predicting CH 4 production from intake parameters (Yan et al, 2009;Nielsen et al, 2013) and most likely caused by variation in the measurement of rumen VFA and OM digestion as demonstrated before in a theoretical simulation study by Bannink et al (2006). Using l CH 4 /kg DMI as the unit strongly decreased variation compared with l CH 4 /day because DMI is the major determinant for variation in CH 4 production.…”
Section: Discussionsupporting
confidence: 84%
“…There were similarities in dietary characteristics and intakes among the databases used by Ellis et al (2007), Yan et al (2009, Ricci et al (2013), Moraes et al (2014, heifers and steers) and our high-forage data set, as indicated by the ranges for the variables. The SD for daily nutrient intakes (DMI, NDF, ADF, starch and fat) indicate that ranges overlapped among the databases used in the various studies even though the means were not the same across the databases.…”
Section: Discussionmentioning
confidence: 57%
“…Despite commonality of data, the prediction equations from those two studies used different approaches and generally did not share common variables. Ellis et al (2009), Yan et al (2009, Moraes et al (2014) Table S2); R 2adj = adjusted coefficient of determination; r c = concordance coefficient correlation; C b = bias factor; RMSPE = root mean square prediction error; ECT% = error due to overall bias of prediction as percentage of mean square prediction error (MSPE); ER% = error due to deviation of the regression slope from unity as percentage of MSPE; ED% = random or disturbance error as percentage of MSPE; MEF = model efficiency; GEI = gross energy intake; S = steers; GEL = gross energy level; DL = dietary level; AL = animal level. Table S2); GEI = gross energy intake; S = steers; GEL = gross energy level; DL = dietary level; AL = animal level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations